A hybrid polymer/oxide/ionic-liquid solid electrolyte for Na-metal batteries. Issue 14 (7th March 2017) - Song, Shufeng; Kotobuki, Masashi; Zheng, Feng; Xu, Chaohe; Savilov, Serguei V.; Hu, Ning; Lu, Li; Wang, Yu; Li, Wei Dong Z.
Abstract : The development of solid electrolytes with superior electrical and electrochemical performances for the room-temperature operation of sodium (Na)-based batteries is at the infant stage and still remains a challenge. Abstract : The development of solid electrolytes with superior electrical and electrochemical performances for the room-temperature operation of sodium (Na)-based batteries is at the infant stage and still remains a challenge. Herein, we, for the first time, report hybrid solid electrolytes consisting of PEO20 –NaClO4 –5% SiO2 – x % Emim FSI ( x = 50, 70) designed for solid-state Na-metal batteries. The hybrid design yields a solid electrolyte featuring a high room-temperature ionic conductivity of 1.3 × 10 −3 S cm −1, suitable mechanical property, a wide voltage stability window of 4.2 V and a high Na + transference number of 0.61. A prototypical Na-metal battery using this hybrid solid electrolyte demonstrates promising long-term cycling performances at room temperature and at an elevated temperature of 60 °C for 100 cycles. The finding implies that the hybrid solid electrolyte is promising for Na-metal batteries operating at room temperature.